The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1038/s41409-020-0833-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective trial of vaccine to prevent hepatitis B virus reactivation after hematopoietic stem cell transplantation

Abstract: Hepatitis B virus (HBV) reactivation reportedly occurs frequently after hematopoietic stem cell transplantation (HSCT) in resolved HBV-infected patients. Here, 50 patients with resolved HBV infections and scheduled to undergo HSCT were enrolled; all subjects were vaccinated with three doses of hepatitis B vaccine 12 months after HSCT and the incidence of HBV reactivation was monitored. The patients' characteristics were: median age, 61 (34-72) years; male/female, 27/19; allogeneic/autologous, 40/6; bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Data from Asia-Pacific region observed 6%-29% risk of HBVr in resolved HBV patients receiving HSCT without antiviral prophylaxis [65,[79][80][81]. A meta-analysis showed that lymphoma patients receiving rituximab-containing regimens had significantly higher risk of HBVr than those receiving non-rituximab-containing regimens (10% vs 4%) [82].…”
Section: Hbsag (−)/Anti-hbc (+) Patients (Table 2)mentioning
confidence: 99%
“…Data from Asia-Pacific region observed 6%-29% risk of HBVr in resolved HBV patients receiving HSCT without antiviral prophylaxis [65,[79][80][81]. A meta-analysis showed that lymphoma patients receiving rituximab-containing regimens had significantly higher risk of HBVr than those receiving non-rituximab-containing regimens (10% vs 4%) [82].…”
Section: Hbsag (−)/Anti-hbc (+) Patients (Table 2)mentioning
confidence: 99%
“…There is a consensus that these patients should have prophylactic treatment with either entecavir or tenofovir if they were to undergo chemotherapy or potent immunosuppression. There have been few small studies with discordant results after HBV vaccination in those with occult HBV infection 74 , 75 . Based on the current evidence, there is no role for HBV vaccination in these patients.”…”
Section: Hepatitis B Vaccinementioning
confidence: 99%
“…None of the 21 patients in the vaccine group developed HBVr, which indicated that HBV vaccination of HSCT recipients was a promising method for preventing HBVr. However, the following multicenter prospective clinical research of hepatitis B vaccine to prevent HBVr after allo-HSCT failed to find the protective role of hepatitis B vaccine in minimizing the risk of HBVr in HBV-resolved recipients ( 31 ). Only 37% (10/27) of patients had HBsAb with three doses of hepatitis B vaccine 12 months after HSCT, and the 2-year cumulative incidence of HBVr was 27.3%.…”
Section: Hbv Vaccine Issuesmentioning
confidence: 99%